2011
DOI: 10.1089/ten.tea.2010.0710
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Nanoparticle-Enhanced Photoacoustic Stimulus for Bone Tissue Engineering

Abstract: In this study, we introduce a novel nanoparticle-enhanced biophysical stimulus based on the photoacoustic (PA) effect. We demonstrate that the PA effect differentiates bone marrow-derived marrow stromal cells (MSCs) grown on poly(lactic-co-glycolic acid) (PLGA) polymer films toward osteoblasts. We further show that the osteodifferentiation of the MSCs due to PA stimulation is significantly enhanced by the presence of single-walled carbon nanotubes (SWCNTs) in the polymer. MSCs, without the osteogenic culture s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Alizarin Red S stains extracellular calcium and is used as a marker for osteo-differentiation of stem cells [22,27]. Figure 5 shows representative images of MSCs stained with Alizarin Red S for calcium deposits after treatment with 0 (Control), 10, or 50 µg/ml of MSNPs or WSNTs for 24 h and incubation in osteogenic differentiation media for 14 days.…”
Section: Resultsmentioning
confidence: 99%
“…Alizarin Red S stains extracellular calcium and is used as a marker for osteo-differentiation of stem cells [22,27]. Figure 5 shows representative images of MSCs stained with Alizarin Red S for calcium deposits after treatment with 0 (Control), 10, or 50 µg/ml of MSNPs or WSNTs for 24 h and incubation in osteogenic differentiation media for 14 days.…”
Section: Resultsmentioning
confidence: 99%
“…Typically, carbon nanomaterial dispersed polymeric scaffolds have been investigated for biomedical applications [9, 52, 7072], however, compared to these composite architectures, 3D all-carbon scaffolds may possess additional multifunctional attributes. The chemical, physical and electrical properties of these 3D CNT scaffolds could be exploited to develop stimulus responsive scaffolds to deliver drugs[19, 20], electroceuticals applications[73], non-invasively image the scaffolds to track tissue regeneration[74] and control the fate of progenitor cells [17, 18]. Therefore, in a true-sense, 3D macroporous all-carbon scaffolds may be exploited as multifunctional scaffolds for the next generation of tissue engineering and regenerative medicine applications.…”
Section: Discussionmentioning
confidence: 99%
“…Carbon nanomaterials such as fullerenes, carbon nanotubes and graphene exhibit excellent physiochemical properties such as high mechanical strength, and electrical conductivity as well as unique electromagnetic, opto-acoustic response, and thus, their multifunctional characteristics have been exploited for several biomedical applications such as bioimaging[1416], stem cell applications[17, 18], drug and gene delivery[19, 20], and photodynamic therapy [21, 22]. They have also been incorporated into polymeric scaffolds as mechanical reinforcing agents [23, 24] or contrast agents [25] to improve non-invasive imaging of the structural properties and biological response of polymeric scaffolds (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been shown that daily PA excitation of native or SWNT-loaded MSCs facilitates differentiation of cells to osteoblasts. 20,92 There is also a wide array of therapeutic applications requiring implantation or insertion of metallic or other optically absorbing devices. During such procedures, localization is critical for ensuring appropriate delivery of the device.…”
Section: Therapy Guidancementioning
confidence: 99%